2014
DOI: 10.1007/s00520-013-2099-6
|View full text |Cite
|
Sign up to set email alerts
|

Experience of meaning in life in bereaved informal caregivers of palliative care patients

Abstract: Coping with the loss of a loved one is associated with changes in MiL framework and considerably impairs a carer's experience of MiL fulfillment. Individual MiL is associated with well-being in PC caregivers during early bereavement. Specific interventions for carers targeted at meaning reconstruction during palliative care and bereavement are needed to help individuals regain a sense of meaning and purpose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 45 publications
0
30
0
1
Order By: Relevance
“…6e10 Some research in this field has shown a direct relationship between the loss of MiL and increased psychological distress. 2,11 Conversely, an increased sense of MiL has been linked to greater psychological well-being 2,9,12 and even to less mortality. 13 A recent study of cancer patients 14 found that MiL acts as a mediating variable in relation to the wish to hasten death that may arise as a result of the physical suffering associated with advanced illness.…”
Section: Introductionmentioning
confidence: 99%
“…6e10 Some research in this field has shown a direct relationship between the loss of MiL and increased psychological distress. 2,11 Conversely, an increased sense of MiL has been linked to greater psychological well-being 2,9,12 and even to less mortality. 13 A recent study of cancer patients 14 found that MiL acts as a mediating variable in relation to the wish to hasten death that may arise as a result of the physical suffering associated with advanced illness.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it seems to operate as a facilitator of adaptive coping (Brandstatter et al, 2014;Kraus, Rodrigues, & Dixe, 2009;Park, Park, & Peterson, 2010;Wnuk, Marcinkowski, & Fobair, 2012), functioning as a tool that allows for greater resistance to suffering and a better adaptation to the disease (Baumeister & Vohs, 2002;Kraus et al, 2009;Sherman & Simonton, 2012;Vehling et al, 2011).…”
mentioning
confidence: 99%
“…Lin et al in a study on the resilience of parents with children with chronic diseases, identi ed acceptance of fate as an important factor in developing resilience in caring for their children [22]. Bandstatter et al identi ed purpose and meaning in life as important factors in stress management in family caregivers who care for end-of-life patients [23]. In relation to the third theme in this study, that is feeling helpless and experiencing loneliness leading to a sense of shame, this may be a product of social rejection externally or of a fear of contracting the virus, an intrinsic motivator for isolation.…”
Section: Discussionmentioning
confidence: 99%